Dieulafoy's lesion of the rectum - Gul, Y.A.; Jabbar, M.F.; Karim, F.A.; Moissinac, K. (ARSMB-KVBMG, 2002)
Dieulafoy's lesion is an uncommon cause of gastrointestinal haemorrhage. It may present with massive and life threatening bleed and although more common in the upper gastrointestinal tract, it is being increasingly reported as affecting the lower gastrointestinal tract. Diagnosis is usually achieved during proctoscopic and endoscopic visualization. In cases where there is profuse and torrential haermorrhage, angiography may help to confirm the diagnosis. There are a few treatment options available, all of which have a varying degree of success. More commonly than not, a combination of treatment is warranted as illustrated by our case. Recurrent bleeding may occur just as in cases of Dieulafoy's lesion affecting the upper gastrointestinal tract. Even though endoscopic visualization of the lower gastrointestinal tract in the presence of profuse lower gastrointestinal haemorrhage may not be possible, this important procedure should not be omitted as the bleeding source may be lying in a low and accessible location for prompt interventional haemorrhage control.